Digitalization and Inclusive Learning Reconstructing Lifelong Education Systems under SDG 4 - Bao, Hui; Li, Xinrui (INTI International University, 2025)
Educational equity and quality remain key challenges in achieving Sustainable Development Goal 4 (SDG 4), especially as globalization and digitalization reshape education systems. Existing research lacks empirical evidence on how digital tools specifically promote inclusive lifelong education and fails to sufficiently address disparities in learning outcomes across socioeconomic groups. To fill these gaps, this study uses a mixed-methods approach, combining quantitative surveys (350 students: 300 from Hope College, Southwest Jiaotong University; 50 from remote Liangshan Prefecture) and qualitative semi-structured interviews, with data collected via Chaoxing Learning Platform and Yuketang. Quantitative analysis (SPSS/R) revealed: 1) 85% of total participants (n=328 valid responses) reported improved accessibility/convenience of digital learning; 2) a positive correlation between digital tool use frequency and test scores (r=0.62, p<0.01). Qualitative content analysis highlighted blended learning’s effectiveness in meeting diverse needs but also indicated potential exacerbation of educational inequalities by digital environments. The findings confirm digital technology’s role in advancing educational resource equalization, providing data-driven insights for policymakers to optimize inclusive lifelong education systems.